2006
DOI: 10.1038/sj.npp.1301153
|View full text |Cite
|
Sign up to set email alerts
|

L-DOPA Disrupts Activity in the Nucleus Accumbens during Reversal Learning in Parkinson's Disease

Abstract: Evidence indicates that dopaminergic medication in Parkinson's disease may impair certain aspects of cognitive function, such as reversal learning. We used functional magnetic resonance imaging in patients with mild Parkinson's disease to investigate the neural site at which L-DOPA acts during reversal learning. Patients were scanned both ON and OFF their normal dopamine-enhancing L-DOPA medication during the performance of a probabilistic reversal learning task. We demonstrate that L-DOPA modulated reversal-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
210
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(239 citation statements)
references
References 58 publications
24
210
2
3
Order By: Relevance
“…The present data suggest that dopaminergic modulation of neural activity in the putamen is especially important when subjects change their behavior on the basis of negative feedback. These findings support a model of executive control in which dopaminergic signals originating in the striatum facilitate the flexible updating of new goal-related representations (Frank et al, 2001;Cools et al, 2007b).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The present data suggest that dopaminergic modulation of neural activity in the putamen is especially important when subjects change their behavior on the basis of negative feedback. These findings support a model of executive control in which dopaminergic signals originating in the striatum facilitate the flexible updating of new goal-related representations (Frank et al, 2001;Cools et al, 2007b).…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, the putaminal region in which methylphenidate modulated BOLD signal in the present study is different from the ventral striatal region in which levodopa modulated BOLD signal in patients with Parkinson's disease during reversal learning (Cools et al, 2007b). One possible reason for this discrepancy is that the study by Cools et al (2007b) involved patients with presumably abnormal dorsal striatal dopamine levels.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…For example, this region of the striatum has been found to be associated with reversal learning in monkeys bearing lesions of the caudate nucleus (Divac et al, 1967). Consistent with an effect at striatal dopamine receptors, raclopride administration in rhesus monkeys produced marked reversal learning impairments (Lee et al, 2007), and in humans, L-DOPA impaired probabilistic reversal learning in patients with Parkinson's disease (Swainson et al, 2000;Cools et al, 2001) and abolished the reversal-related blood oxygen level-dependent (BOLD) signal in the nucleus accumbens (Cools et al, 2007a).…”
Section: Discussionmentioning
confidence: 85%
“…Such effects can be explained by different hypothesized "inverted U"-shaped relationships between performance on different tasks and PFC dopamine, at the systems (Williams and Goldman-Rakic, 1995;Mattay et al, 2003;Roberts et al, 1994) or cellular (Vijayraghavan et al, 2007) levels. Such relationships have been postulated in humans (Cools et al, 2001(Cools et al, , 2007a but not demonstrated for the striatum.…”
Section: Introductionmentioning
confidence: 95%